Role of peripheral pan-retinal photocoagulation in diabetic macular edema treated with intravitreal ziv-aflibercept - Mansour, Ahmad M (Clin Ophthalmol, 2019)
PURPOSE: The aim of this study was to investigate the possibility of decreasing the number of intravitreal anti-VEGF by peripheral pan-retinal photocoagulation (PPRP) in managing diabetic macular edema (DME) in a subcategory of patients who cannot comply to strict anti-VEGF follow-up protocols. MATERIALS AND METHODS: This is a pilot prospective study. Consecutive patients with naïve DME were offered the choice of treatment and extend intravitreal ziv-aflibercept if they showed willingness for good compliance or PPRP with modified pro re nata intravitreal injections. RESULTS: Six eyes of 3 patients had PPRP versus 4 eyes of 4 patients had injections only. The number of anti-VEGF injections was markedly decreased when PPRP was administered from a mean number of injections of 16.8 (range 13–21; mean follow-up 24.3 months) to a mean number of 4.5 (range 0–8; mean follow-up 33.7 months). Mean initial central macular thickness (CMT) was 462.0 mm in the injection only group vs 457.3 mm in the PPRP group. Mean final CMT was 462.0 in the injection only group vs 350.0 in the PPRP group. Baseline and final mean logMAR (Snellen equivalent) best-corrected visual acuity was initially and finally 0.84 (20/137) and 0.60 (20/80) in the injection only group and 0.70 (20/100) and 0.69 (20/98) in the PPRP group, respectively. The monthly cost for the PPRP group was one-third of the monthly cost for the injection only group. CONCLUSION: PPRP allowed for a decrease in the number of intravitreal anti-VEGF injections in selected DME patients (sick, difficult to ambulate, financial burden, and fear of injections).